Verification of sensitivity analysis method of measurement uncertainty evaluation. (December 2021) - Wojtyła, Mirosław; Rosner, Paweł; Forbes, Alistair B.; Savio, Enrico; Balsamo, Alessandro
Abstract: A research work is presented, carried out to validate a method based on sensitivity analysis for evaluating the uncertainty of CMM measurements. The fitness for purpose of cylinder squares for verifying the uncertainty evaluation of coaxiality measurements has been confirmed. Ring gauges too were used and found useful, but only as to its diameter. A type B method for predicting the uncertainty considering the actual technical condition of the CMM is proposed.